The influence of alloying with manganese and chromium of steel hardened and tempered auger on its relative wear resistance during dehydration in a municipal solid waste truck - Bereziuk, O.V.; Savulyak, V.I.; Kharzhevskyi, V.O. (Problems of Tribology, 2022)
The article is dedicated to the study of the influence of alloying with manganese and chromium followed by hardening and tempering of the auger on its wear resistance during the dehydration of municipal solid waste truck. The use of a mathematical apparatus and appropriate regression analysis programs made it possible to determine the dependence of the wear resistance of the auger on the content of manganese and chromium in the steel of the auger for the case of its quenching and tempering. Constructed graphical dependences of relative wear resistance with the indicated alloying and heat treatment of the screw revealed a significant influence of the concentration of manganese and chromium in steel, sufficient convergence of the obtained patterns was confirmed. It was established that after operation and wear on the path s = 56850 m during the dehydration of solid waste in a garbage truck, an increase in the manganese content in the steel of the heat-treated screw from 0.32% to 1.8% leads to a decrease in energy intensity by 10 kWh/tons, and an increase chromium content in screw steel after similar heat treatment from 0% to 6% leads to a decrease in energy consumption by 11.5 kWh/tons and to a reduction in the cost of the solid waste dehydration process in the garbage truck. It was determined that tempering the chromium-manganese screw steel after its hardening allows reducing energy consumption by 1.26...2.56 kWh/tons, depending on the chromium content. The expediency of conducting further research on determining the rational composition and structural state of the auger material and ways to increase its wear resistance has been revealed